2017
DOI: 10.1111/cei.13007
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor regulation and production by macrophages in osteoarthritic synovium

Abstract: Nerve growth factor (NGF) functions to modulate osteoarthritis (OA)-associated pain. Although recent studies suggest that tumour necrosis factor (TNF)-α and interleukin (IL)-1β mediate NGF activity in human synovial fibroblasts, the regulation of NGF expression in human synovial macrophages remains unclear. Here, we examined the role of macrophages in the production and regulation of synovial (SYN) NGF in osteoarthritic knee joints by examining the mRNA expression of TNF-α and IL-1β in freshly isolated CD14-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 26 publications
3
70
0
Order By: Relevance
“…Our results of NGF localized inside the macrophages could possibly be explained by its paracrine action meaning that it is taken up by cells through the TrkA/p75NTR receptor complex or that it is located in cells or/and structures that are phagocytosed by macrophages. Our observation is partially supported by a study where it has been shown that both the NGF-mRNA and the NGF protein were detected in macrophages isolated from patient with osteoarthritis [66], whereas the NGF-mRNA was also found in cultured mouse macrophages [67]. In general, it is supported that the neurotrophic factor NGF regulates in a paracrine way the migration of monocytes/macrophages into the CNS through the BBB [68].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results of NGF localized inside the macrophages could possibly be explained by its paracrine action meaning that it is taken up by cells through the TrkA/p75NTR receptor complex or that it is located in cells or/and structures that are phagocytosed by macrophages. Our observation is partially supported by a study where it has been shown that both the NGF-mRNA and the NGF protein were detected in macrophages isolated from patient with osteoarthritis [66], whereas the NGF-mRNA was also found in cultured mouse macrophages [67]. In general, it is supported that the neurotrophic factor NGF regulates in a paracrine way the migration of monocytes/macrophages into the CNS through the BBB [68].…”
Section: Discussionsupporting
confidence: 79%
“…Our observation is made for the first time in the EAE model in high percentage. In studies employing human peripheral blood monocytes, the results are unclear as expression of NGF, TrkA, and p75NTR is reported in monocytes but not in macrophages and in a macrophage subpopulation isolated from patients with osteoarthritis [63][64][65][66]. The question that derives is whether macrophages synthesize and secrete NGF.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β mRNA expression was increased in immobilized muscle . IL‐1β plays a critical role in various pain states, such as neuropathic pain and osteoarthritis, through upregulation of NGF. Our observations of increased NGF level in immobilized muscle may be due to an accumulation of M1 macrophages as well as upregulation of IL‐1β.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells can produce neurotrophic factors, which are key mediators of new nerve outgrowth, and in particular, macrophages are proficient producers of neurotrophins, 36,37 including BDNF, 38,39 GDNF, 40 and NGF. [41][42][43] We have previously shown that NGF is a key element controlling nerve fiber sprouting in the colonic mucosa of patients with IBS. 11 Macrophage has been involved in nerve sprouting in different tissues.…”
Section: Discussionmentioning
confidence: 99%